Transcranial magnetic stimulation over posterior parietal cortex modulates alerting and executive control processes in attention. (12th October 2022) - Middag‐van Spanje, Marij; Duecker, Felix; Gallotto, Stefano; de Graaf, Tom A.; van Heugten, Caroline; Sack, Alexander T.; Schuhmann, Teresa
Abstract: Attention includes three different functional components: generating and maintaining an alert state (alerting), orienting to sensory events (orienting), and resolving conflicts between alternative actions (executive control). Neuroimaging and patient studies suggest that the posterior parietal cortex (PPC) is involved in all three attention components. Transcranial magnetic stimulation (TMS) has repeatedly been applied over the PPC to study its functional role for shifts and maintenance of visuospatial attention. Most TMS‐PPC studies used only detection tasks or orienting paradigms to investigate TMS‐PPC effects on attention processes, neglecting the alerting and executive control components of attention. The objective of the present study was to investigate the role of PPC in all three functional components of attention: alerting, orienting, and executive control. To this end, we disrupted PPC with TMS (continuous theta‐burst stimulation), to modulate subsequent performance on the Lateralized‐Attention Network Test, used to assess the three attention components separately. Our results revealed hemifield‐specific effects on alerting and executive control functions, but we did not find stimulation effects on orienting performance. While this field of research and associated clinical development have been predominantly focused on orienting performance, our results suggest that parietal cortex and its modulation may affect other aspects of attention as well. Abstract : Parietal cortex has been linked to alerting, orienting, and executive control, and the Lateralized‐Attention Network Test captures these attention processes. Right parietal TMS affected alerting and executive control, not orienting. Results emphasize functional PPC contributions to a range of attention mechanisms, and future TMS‐PPC research would benefit from a more inclusive approach.